Europeanization and Tolerance in Turkey The Myth of Toleration - Kaya, A.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
The book questions the popularity of the notion of tolerance in Turkey, and argues that the regime of tolerance has been strengthened in parallel with the Europeanization process, which has boosted the rhetoric of the Alliance of Civilizations in a way that culturalized what is social and political.
Keywords: Religion and sociology; Ethnology—Europe.; Europe—Politics and government; Ethnicity; Political sociology; European Union; Social Aspects of Religion; European Culture; European Politics; Ethnicity Studies; Political Sociology; European Union Politics